2012
DOI: 10.1515/1553-3840.1534
|View full text |Cite
|
Sign up to set email alerts
|

The Microalga Spirulina platensis Presents Anti-inflammatory Action as well as Hypoglycemic and Hypolipidemic Properties in Diabetic Rats

Abstract: Spirulina platensis (Spi) is a microalga presenting high contents of proteins, γ-linolenic acid, vitamins and minerals, and showing many biological activities. It is a promising drug for the treatment of diseases including diabetes. The objectives of this work were to study Spi effects on alloxan-induced diabetic rats, and associate this to its anti-inflammatory activity. The treatment with Spi (25, 50 or 100 mg/kg, p.o.) started 48 h after the alloxan injection, continuing for 5 or 10 days. Biochemical parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 0 publications
3
36
1
2
Order By: Relevance
“…Previous studies from our group in Brazil showed that the oral administration of SPI for 5 or 10 days, at the doses of 25, 50 and 100 mg/kg/day, significantly reduced glucose, triglyceride and cholesterol levels in alloxan induced diabetic rats [5]. Other groups have shown that SPI exhibited hypolipidemic and hypoglycemic activities through the lowering of blood glucose levels, regulating cholesterol and triglyceride and improving insulin resistance in Figure 5.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Previous studies from our group in Brazil showed that the oral administration of SPI for 5 or 10 days, at the doses of 25, 50 and 100 mg/kg/day, significantly reduced glucose, triglyceride and cholesterol levels in alloxan induced diabetic rats [5]. Other groups have shown that SPI exhibited hypolipidemic and hypoglycemic activities through the lowering of blood glucose levels, regulating cholesterol and triglyceride and improving insulin resistance in Figure 5.…”
Section: Discussionmentioning
confidence: 71%
“…The anti-inflammatory effect of SPI was further confirmed by a decrease in TNFα immunostaining in the inflamed paw and in the myeloperoxidase release from human neutrophils [5].…”
Section: F a De Oliveira Garcia Et Almentioning
confidence: 77%
See 1 more Smart Citation
“…[11][12][13] This is attributed to the synergistic action of its components such as antioxidant pigments, phycobiliproteins, carotenes, vitamins C and E, c-linolenic acid, and phenolic compounds. 14,15 The antioxidant effect of Spirulina may be responsible for its multiple pharmacological activities, which include antiviral, 16 hypoglycemic, 17 hypolipidemic, 11 anticarcinogenic, 18 antianemic, 19 and antiinflammatory 20 properties. It has been shown that the consumption of Spirulina can prevent different pathologies associated with oxidative stress and inflammation.…”
Section: Introduction Imentioning
confidence: 99%
“…Studies have also demonstrated that vitamin C is more potent in preventing LDL oxidation thereby reduced the risk of development of atherosclerosis in DM. SP contains good quality proteins which might stimulate insulin secretion and such effect may be responsible for the reduction in FBGL [20][21] .…”
Section: Fig 2: Values Are Expressed As Mean±sem (N=6); Superscriptsmentioning
confidence: 99%